Early Marriage, Human Rights, and the Living Fiqh: A Maqasid al-Shariʻa Review - Kurniawan, Edi; Handesman, Handesman; Rahmadi, Rahmadi; Najib, Khairun (Al-Risalah, 2020)
Human rights activists and the educated urban society strongly criticize the practice of early marriage, including the classical fiqh on which it is based. They have repeatedly proposed amendments to article 7 of the Marriage Law No. 1 of 1974 concerning age restrictions on marriage. This paper is a response to these groups’ views with the formulations, first, what are the factors and the problems of early marriage and their status in the perspective of maqāṣid al-sharīʻa?; second, what worldview that projects the human rights activists’ criticism in the midst of living fiqh and maqāṣid al-sharīʻaʼs review on it? This paper is a combination of field and literary studies. Samples are taken from the living fiqh or the doctrine of Shāfiʻī School which exists in the Malay community of Tebo Ulu, Jambi Province and supported by relevant literature. This paper concludes that, in early marriage, the harms are far greater than the benefits. Hence, according to the holistic understanding of maqāṣid al-sharīʻa, the marriageable age needs to be regulated by law. However, the above groups’ criticism is not completely justifiable because early marriage is also closely related to the state's failure in improving the welfare of its citizens, providing educational facilities, as well as differences in worldview between human rights activists and article 284 of the Criminal Law Code on adultery and traditional customs of Malay and other Indonesia’s indigenous custom that need to be resolved.